Mechanical performance of cement- and screw-retained all-ceramic single crowns on dental implants - Obermeier, Matthias; Ristow, Oliver (Clinical oral investigations, 2018)
This in-vitro study was performed to compare the contact wear, fracture strength and failure mode of implant-supported all-ceramic single crowns manufactured with various fabrication and fixation concepts.